(untitled) (Bangladesh Journal of Medical Science, 2021)
Background and methodology: In the current study magnetic poly(ethylene glycoldimethacrylate-N-methacryloyl-(L)-histidine methyl ester) poly(Egdma–Mah)) was used as ametal chelated affinity particles. Cu2+ ions loaded directly to MAH ligand of magnetic particlesfor the adsorption of cytochrome c (Cyt c) in a continuous flow system. Results: The maximumCyt c adsorption capacity on the magnetic particles and Cu2+-chelated magnetic particles were42 mg/g and 197 mg/g in phosphate buffer (pH 8.0), respectively. Cu2+ loading increased theCyt c adsorption capacity, significantly. Cyt c adsorption capacity decreased with increasedtemperature and with increasing magnetic field. According to reusability studies Cyt c moleculescould be reversibly adsorbed and desorbed five times. The binding isotherm was determined byscatchard analysis followed by application of Hill equation to the data obtained, then bindingconstant and nH Hill coefficient were calculated. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.159-163